Enhanced spin–orbit torques by oxygen incorporation in tungsten films - Demasius, Kai-Uwe (Nat Commun, 2016)
The origin of spin–orbit torques, which are generated by the conversion of charge-to-spin currents in non-magnetic materials, is of considerable debate. One of the most interesting materials is tungsten, for which large spin–orbit torques have been found in thin films that are stabilized in the A15 (β-phase) structure. Here we report large spin Hall angles of up to approximately –0.5 by incorporating oxygen into tungsten. While the incorporation of oxygen into the tungsten films leads to significant changes in their microstructure and electrical resistivity, the large spin Hall angles measured are found to be remarkably insensitive to the oxygen-doping level (12–44%). The invariance of the spin Hall angle for higher oxygen concentrations with the bulk properties of the films suggests that the spin–orbit torques in this system may originate dominantly from the interface rather than from the interior of the films.